2017
DOI: 10.1515/jcim-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of the aqueous extract of the flowers of Nymphaea lotus Linn (Nymphaeaceae): Acute, neuro- and subchronic oral toxicity studies in albinos Wistar rats

Abstract: Background Nymphaea lotus Linn (N. lotus) is a medicinal plant widely used in Cameroon popular medicine, to treat neuropsychiatric conditions, male sexual disorders or as food supplement. However, scientific data on the pharmacotoxic profile of this plant are not available. The safety of N. lotus was assessed in acute, neuro- and subchronic toxicity studies by following the OECD guidelines. Effectively, no data have been published until now in regard to its safety on the nervous system. Methods Aqueous extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Many research teams have conducted studies focusing on N. lotus in several aspects. The safety of N. lotus flower extracts was verified by Kameni et al [10]. Acute, sub-chronic and neurotoxicity were studied in vivo using an albinos Wistar rat model.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many research teams have conducted studies focusing on N. lotus in several aspects. The safety of N. lotus flower extracts was verified by Kameni et al [10]. Acute, sub-chronic and neurotoxicity were studied in vivo using an albinos Wistar rat model.…”
Section: Introductionmentioning
confidence: 93%
“…Acute, sub-chronic and neurotoxicity were studied in vivo using an albinos Wistar rat model. This study indicated that the N. lotus flowers extract probably account for neuroprotective, immune-boosting and antioxidant activity without neurotoxicity [10]. Furthermore, the pharmacological and medicinal potential of this medicinal species were currently confirmed at in vivo level, i.e., anti-diarrhea effect of N. lotus rhizome extract [5], anxiolytic and antidepressant potential from the N. lotus leaf extract [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, Thailand, Indonesia and a large number of Asian countries, almost every part of N. lotus has long been consumed as a vegetable [3,5,[7][8][9]13,[15][16][17]. As an important ingredient for formulating Asian traditional medicines, particularly for circulatory system syndrome, several parts of this plant, such as root, leaves and flower parts, have been used since ancient times [1,7,13].…”
Section: Traditional Usesmentioning
confidence: 99%
“…We may observe that much of the cosmetic potential of this plant is primarily based on its high accumulation of flavonoids, mostly in its flower parts [5,6,11]. In addition, many studies have confirmed its toxicological safety, which is a good argument for future applications [7,10,13,18].…”
Section: Traditional Usesmentioning
confidence: 99%
See 1 more Smart Citation